ENHANCING TEACHING EFFECTIVENESS THROUGH DESIGN THINKING TRAINING: A STUDY OF ENGINEERING FACULTY IN CHENNAI - Beula, Hepsiba; Radhakrishnan, M. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The dynamic nature of the engineering education requires the implementation of new pedagogical methods that help to boost teaching performance and the learning results of the students. It explores the effect of design-thinking training on faculty teaching performance in engineering colleges in Chennai and the mediating role played by design-thinking self-efficacy and institution-level support in particular. The design of the quantitative research was conducted with the help of a structured questionnaire that was conducted with the members of the faculty that underwent training in design-thinking. Analysis of data was conducted based on statistical methods, such as descriptive analysis, correlation, and Structural Equation Modeling (SEM) to compare both direct and mediated relationships. Findings indicate that faculty training on design thinking positively influences teaching effectiveness to a great extent, which proves its ability to change traditional teaching methods into more interactive and student-focused teaching methods. Moreover, the design-thinking self-efficacy was identified as a powerful mediator, which means that the faculty confidence in implementing the design-thinking methodologies is a key factor in increasing the teaching outcomes. The significance of organizational resources, leadership, and innovation culture in facilitating pedagogical change was also found, which is due to the significant mediating effect of institutional support. The research has added to the literature by giving a combined model, which explicates the role of the faculty training on teaching effectiveness via personal and institutional process. The implications of the findings to academic institutions and policymakers can be seen in the fact that the proposed strategies will be useful to develop effective faculty development plans and promote innovation-based teaching and learning environments.